AKTIVITAS PROBIOTIK BAKTERI Enterococcus lactis SA8 ASAL SUSU KERBAU SUMBAWA (Bubalus bubalis): PROBIOTIC ACTIVITY OF Enterococcus lactis SA8 BACTERIA FROM SUMBAWA BUFFALO MILK (Bubalus bubalis) - Harmoko, Deni; Ningrum, Rizka Kusuma; Pati, Andra Alvianto Umbu (Jurnal SainHealth, 2024)
The most important quality of lactic acid bacteria as probiotics used for additives is tolerance to bile salts and low pH, which allows bacteria to survive, grow, and provide therapeutic effects in the digestive tract. Probiotics are living microorganisms that can provide optimal health effects when consumed in certain amounts, even exceeding general nutrition. Lactic acid bacteria are probiotic bacteria that can provide good health benefits when consumed regularly. The growth and production of lactic acid in LAB are influenced by pH and bile salts, this ability distinguishes between species of lactic acid bacteria. LAB must have The main physiological requirements of probiotic bacteria are their resistance and tolerance to low pH and bile salts. This study aims to test E. lactis SA8 bacteria from Sumbawa Buffalo milk to determine their probiotic activity through tests on pH resistance and their ability to live in bile salts. E. lactis SA8 bacteria have probiotic activity, which is indicated by their ability to withstand low pH, and the results of bile salt testing show the highest viability at a concentration of 0.3% with a density of 9.8x107 CFU/mL, which is a sign of probiotic bacteria.  Keywords: Probiotics, lactic acid bacteria, Enterococcus lactis SA8, pH and bile salt tests